Petroleum potentiality of the Balambo Formation in Bekhme and Razan sections, Kurdistan region, northeastern Iraq - Srood F. Naqshabandi; Wrya Mamaseni; Bzhar A. Delizy; Goran F. Hasan (Tikrit Journal of Pure Science)
Balambo Formation (Early Cretaceous) had been studied in Razan and Bekhme sections, Erbil Governorate, Kurdistan Region-Iraq, to determine the hydrocarbon generation potentiality for the studied rocks. The samples were analyzed for TOC, Rock Eval pyrolysis and GC-MS technique. The Balambo Formation’s TOC wt. % content is relatively high, ranging between 0.95 to 7.59 wt.% (average 2.91 wt.%). The Formation has the potentiality to generate gas and oil owing to its suboxic-anoxic depositional environment, marine origin organisms, suitable maturity level, and the type of kerogen is predominantly types III and subordinate amount of mixed type II-III according to the Rock-Eval pyrolysis data and isoprenoid/n-alkane. The C27%, C28% and C29% regular steranes distribution suggested the studied formation is deposited in marine environment. The samples were proven to be mature based on the ratios of the Tmax, steranes 20S/ (20S+20R)C29 to ββS/(ββS+ααR)C29 steranes and C32 22S/(22S+22R) hopane. Although the Ts/(Ts+Tm) ratio data point to an early mature stage, vitrinite reflectance predictions ranged from 0.55 to 0.75%, once more pointing to a mature stage.